2021
DOI: 10.1159/000514431
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effects of Long-Term Metformin Preconditioning on Rats with Ischemic Brain Injuries

Abstract: <b><i>Introduction:</i></b> This study is to analyze the neuroprotective effects of long-term metformin (Met) preconditioning on rats with ischemic brain injuries and the related mechanisms. <b><i>Methods:</i></b> Twenty-five Sprague-Dawley rats were randomly divided into 5 groups: sham group, middle cerebral artery occlusion (MCAO) group, normal saline + MCAO group, pre- Met + MCAO group, and 3-MA + Met + MCAO group. Pathological changes of brain were observed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…To our knowledge, no such direct comparison was previously reported and the data presented here bears relevance to the mechanisms controlling mitochondrial biogenesis and its role in neuroprotection. The preconditioning paradigms, hypoxia and NO treatments, have been extensively tested both in vitro and in vivo studies and induced tolerance in a variety of cells and tissues [28][29][30][31][32]. In this study, we applied the preconditioning methods that were suitable for in vitro treatments of all neuronal cells.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, no such direct comparison was previously reported and the data presented here bears relevance to the mechanisms controlling mitochondrial biogenesis and its role in neuroprotection. The preconditioning paradigms, hypoxia and NO treatments, have been extensively tested both in vitro and in vivo studies and induced tolerance in a variety of cells and tissues [28][29][30][31][32]. In this study, we applied the preconditioning methods that were suitable for in vitro treatments of all neuronal cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, treatment with AMPK activators could attenuate these behavioral and molecular changes in the pathophysiological profile of metabolic dysfunction (Wang et al 2018 ). Various studies have shown that treatment with metformin is effective in neurological diseases, including high MPTP and increased BDNF (Patil et al 2014 , Lu et al 2016 ), Parkinson’s disease (Choi et al 2010 ; Arbeláez-Quintero and Palacios 2017 ; Lu et al 2020 , Paudel et al 2020 ), epilepsy (H S, Paudel et al 2019 , Demaré et al 2021 ; Sanz et al 2021 , Salvati et al 2022 ), traumatic brain injury (Tao et al 2018 ; Taheri et al 2019 ; Fan et al 2020 ; Rahimi et al 2020 ), neuroprotection of the heart (Zhu et al 2018 , Benjanuwattra et al 2020 , Leech et al 2020 ), and preconditioning in ischemic brain injury (Wang et al 2021a , b , c ). Various studies have shown that BDNF can affect the structure of the anal sphincter (Singh and Rattan 2021 , Singh, Singh et al 2021 ).…”
Section: Metformin and Therapeutic Goalsmentioning
confidence: 99%
“…Indeed, metformin administration in STZ-diabetic rats resulted in improved testosterone, LH and FSH hormones levels (Nasrolahi et al 2013 ). Various studies have shown that treatment with metformin is effective in reproductive system diseases, including female and male reproduction in endocrine pathologies (Lee et al 2019 ; Shpakov 2021 , ul haq Shah, Shrivastava et al 2022 ), endometriosis (Zhao et al 2018 , Mu et al 2020 , Stochino-Loi et al 2021 , Kimber-Trojnar et al 2022 ), polycystic ovary syndrome (Chen et al 2019 ; Fornes et al 2022 , Xu et al 2022 ) and prostate (Sun et al 2018 , Chen, Wang et al 2021a , b , c , Aydın et al 2022 , Morale et al 2022 ).…”
Section: Metformin and Therapeutic Goalsmentioning
confidence: 99%
See 1 more Smart Citation
“…LBP protects the hippocampal neuron model of ischemic brain injury in vivo [11]. It also studied the protective effect of LBP in the middle cerebral artery occlusion model in vivo [12]. Recently, it has been reported that LBP could effectively alleviate the degeneration of the nigrostriatal system induced by methyl‐4‐phenyl‐1,2,3,6‐tetrahydropyridine treatment, which might be a potential candidate drug for Parkinson's disease (PD) treatment [13].…”
Section: Introductionmentioning
confidence: 99%